Greater lateral root branching density in maize improves phosphorus acquisition from low phosphorus soil - Jia, Xucun; Liu, Peng; Lynch, Jonathan P (Journal of experimental botany, 2018)
Maize genotypes with greater lateral root branching density have superior phosphorus uptake, growth, and yield in low phosphorus soil. Abstract The development of crops with better growth under suboptimal phosphorus availability would improve food security in developing countries while reducing environmental pollution in developed countries. We tested the hypothesis that maize (Zea mays) phenotypes with greater lateral root branching density have greater phosphorus acquisition from low phosphorus soils. Recombinant inbred lines with either 'many short' (MS) or 'few long' (FL) lateral root phenotypes were grown under high and low phosphorus conditions in greenhouse mesocosms and in the field. Under low phosphorus in mesocosms, lines with the MS phenotype had 89% greater phosphorus acquisition and 48% more shoot biomass than FL lines. Under low phosphorus in the field, MS lines had 16% shallower rooting depth (D95), 81% greater root length density in the top 20 cm of the soil, 49% greater shoot phosphorus content, 12% greater leaf photosynthesis, 19% greater shoot biomass, and 14% greater grain yield than FL lines. These results are consistent with the hypothesis that the phenotype of many, shorter lateral roots improves phosphorus acquisition under low phosphorus availability and merits consideration for genetic improvement of phosphorus efficiency in maize and other crops.